Anxiety as an ethological factor of bruxism - literature (Research, Society and Development, 2020)
Bruxism is a parafunctional habit of multifactorial origin, which causes functional disorders with severe clinical implications. This function may be related to emotional factors, anxiety, and to behavioral characteristics of the individual. The objective of this work was to evaluate the prevalence of bruxism during waking and sleep bruxism describing aspects related to anxiety. Determining the etiological factor is important for diagnosis and treatment, to improve the quality of life of patients with the habit. The present study reviewed the literature on the relationship between bruxism and anxiety, addressing the main ways of treating this dysfunction. The keywords “bruxism”, “anxiety”, “etiology” and “sleep bruxism” were used in the PubMed and VHL databases. The references that dealt with the subjects related to the proposed theme were chosen, published during the last 20 years. He observes that the approach and treatment of the patient with bruxism and anxiety must be multidisciplinary, and that the direct relationship between the two diseases is not easy to be determined, as there is no scientific evidence of sleep bruxism and bruxism in wake. Thus, the evidence elucidates that there is a need for well-designed studies. In addition, the forms of treatment available are numerous, and that to be effective, therapies must be multidisciplinary, depending on the determination of the etiological factors of the two pathologies, and on the assessment of the risks and benefits of each therapy for the patient to be treated.